Consumer practices and perceptions regarding the purchasing and handling of microgreens in the United States. (March 2023) - Yeargin, Thomas A.; Lin, Zhihong; do Prado, Isabelle; Sirsat, Sujata A.; Gibson, Kristen E.
Abstract: Microgreens are a specialty crop which have gained popularity due to their sensory attributes as well as bioactive components. The age (10–14 days from seeding) and size (1–3 inches in height) at which microgreens are harvested distinguish them from other leafy greens. This study aimed to characterize microgreen consumers and determine their knowledge, attitude, and self-reported practices related to microgreens and food safety. A 39-item survey was launched in the U.S. via Qualtrics™ to collect data from April 29th to May 14th, 2021. Data were collected pertaining to consent, eligibility, consumption, purchase, storage, washing, food safety perception, and demographics. Descriptive statistics were performed on all variables to determine frequencies and distribution. Data were collected from qualified individuals (n = 660) across 50 states with an average 9-min completion time. Participants were mostly aged 30–39, with a bachelor's degree, and annual income of $75, 000–149, 999. Approximately one-half of respondents (50.5%) consumed microgreens 1–2 times per week and stored them 6 days or less (80.3%) prior to consumption. Consumers were confident in their ability to safely store and handle microgreens safely 38.9 and 39.8% of the time, respectively, and nearly three-quarters (71.3%) of all consumers washed microgreens. Consumers were mostly ambiguous on whether eating microgreens could result in foodborne illness (24.7%) and felt that microgreens were as safe as fresh produce (37.9%) in general. The results demonstrated that most microgreens consumers exhibit safe practices during the storage and handling of microgreens. However, there was a disconnection between the reported practices and confidence in related knowledge. As most respondents also did not know the difference between a microgreen and a sprout, consumer outreach should address different aspects of microgreens as compared to other produce as well as their associated food safety risks. Highlights: Microgreens consumers overall report safe food handling practices. Many consumers lack clarity on the difference between microgreens and sprouts. There is a disconnect between reported practices and knowledge.